2003
DOI: 10.1016/s0009-9236(03)00006-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simultaneous versus staggered dosing on pharmacokinetic interactions of protease inhibitors

Abstract: Except for saquinavir followed by ritonavir, there is little difference in protease inhibitor exposure for simultaneous or staggered doses. The persistent effect of ritonavir suggests the possibility that lower doses and longer dosing intervals might be effective when ritonavir is used to boost concentrations of other protease inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The inhibition by ritonavir is commonly viewed to occur almost instantaneously and to cease when the drug has been cleared (30). It has been reported that the impact of high doses of ritonavir can last up to 48 h after the dose, despite the short half-life (3 to 5 h) (31). Switching back to standard dosing within 24 to 48 h after discontinuation of LPV/r is likely to be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition by ritonavir is commonly viewed to occur almost instantaneously and to cease when the drug has been cleared (30). It has been reported that the impact of high doses of ritonavir can last up to 48 h after the dose, despite the short half-life (3 to 5 h) (31). Switching back to standard dosing within 24 to 48 h after discontinuation of LPV/r is likely to be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was sampled every 2 hours for 12 hours. Plasma drug levels were determined by HPLC [33]. Doses used in this study were those that resulted in the same area under the curve as seen in humans treated with atazanavir and saquinavir.…”
Section: Methodsmentioning
confidence: 99%
“…Noting this activity, investigators have coadministered ritonavir with saquinavir and found markedly elevated and sustained plasma levels of saquinavir in rat and dog models. This occurred, supposedly, by inhibiting metabolism of saquinavir (10), and this combination is clinically used for individuals with HIV infection (11). On the basis of the pharmacokinetics of ritonavir, a coformulated agent containing lopinavir and ritonavir has been developed: Low doses of ritonavir enhanced the activity of lopinavir (12), and this formulation is being used for first-line therapy for some HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 99%